2010
DOI: 10.1007/s12291-010-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Celastrus paniculatus in Experimentally Induced Hypercholesterolemic Wistar Rats

Abstract: The objective of the present study was to evaluate hypolipidemic effect of methanolic extract of Celastrus paniculatus in experimentally induced hypercholesterolemic rats. Hypercholesterolemia was induced by feeding the animals with high fat diet. Oral administration of methanolic seed extract (50%) of Celastrus paniculatus at the optimized dose of 65 mg/kg body weight, substantially reduced the plasma total cholesterol, triglycerides and LDL cholesterol in comparison with induced hypercholesterolemic animal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 15 publications
2
31
0
6
Order By: Relevance
“…The significant reduction in body weight by the extract in female rats fed with high fat diet may be partly attributed to inhibition of cholesterol deposition in body tissues or inhibition of HMG CoA reductase activity which is the key regulatory enzyme in cholesterol biosynthetic pathway [1,2,27]. This implies that the extract may be recommended for persons who want to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in body weight by the extract in female rats fed with high fat diet may be partly attributed to inhibition of cholesterol deposition in body tissues or inhibition of HMG CoA reductase activity which is the key regulatory enzyme in cholesterol biosynthetic pathway [1,2,27]. This implies that the extract may be recommended for persons who want to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that play a role in lowering cholesterol might be alkaloids and non-alkaloids (Santoso et al, 2010), saponins (Son et al, 2007), polyphenol (Ngamukote et al, 2011;Zang et al, 2006), flavonoid (Shrime et al, 2011). Patil et al (2010) reported that the reduction of cholesterol and triglycerides by alkaloids were in part caused by the reduction of lipogenic enzymes activities and increased bile acid excretion in feces.…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 99%
“…In addition, the high fat content of meats reduce meat taste and increase the risk of metabolic diseases occurrences such as coronary heart disease (Tumova and Teimouri, 2010). In developed countries, consuming of high fat meats was positively correlated with an increase in the risk of incidence of metabolic diseases (Patil et al, 2010). Therefore, feeding low protein diets in broiler chickens needs to be balanced by feed supplement to inhibit rapid deposition of fat.…”
Section: Introductionmentioning
confidence: 99%
“…The various parts such as bark, leaves, and fruits are used in traditional medicine system for various ailments. The bark powder has been found to possess various medicinal properties including cardioprotective properties, anti-ischemic, antioxidant [14], hypercholesterolemia effect [15], antimicrobial [16,17], anti-inflammatory, immunomodulatory, and antinociceptive activity [18]. It is also useful to cure obesity, hypertension, and hyperglycemia [19].…”
Section: Introductionmentioning
confidence: 99%